Searching for Saturn's X-rays during a rare Jupiter Magnetotail crossing using Chandra. Issue 1 (14th June 2021) - Weigt, D M; Dunn, W R; Jackman, C M; Kraft, R; Branduardi-Raymont, G; Nichols, J D; Wibisono, A D; Vogt, M F; Gladstone, G R
ABSTRACT: Every 19 yr, Saturn passes through Jupiter's 'flapping' magnetotail. Here, we report Chandra X-ray observations of Saturn planned to coincide with this rare planetary alignment and to analyse Saturn's magnetospheric response when transitioning to this unique parameter space. We analyse three Director's Discretionary Time (DDT) observations from the High Resolution Camera (HRC-I) on-board Chandra, taken on 2020 November 19, 21, and 23 with the aim to find auroral and/or disc emissions. We infer the conditions in the kronian system by looking at coincident soft X-ray solar flux data from the Geostationary Operational Environmental Satellite ( GOES ) and Hubble Space Telescope ( HST ) observations of Saturn's ultraviolet (UV) auroral emissions. The large Saturn–Sun–Earth angle during this time would mean that most flares from the Earth-facing side of the Sun would not have impacted Saturn. We find no significant detection of Saturn's disc or auroral emissions in any of our observations. We calculate the 3σ upper band energy flux of Saturn during this time to be 0.9–3.04 × 10 −14  erg cm −2  s −1 which agrees with fluxes found from previous modelled spectra of the disc emissions. We conclude by discussing the implications of this non-detection and how it is imperative that the next fleet of X-ray telescope (such as Athena and the Lynx mission concept) continue to observe Saturn with their improved spatial and spectral resolution and very enhanced sensitivity to help us finally solve the mysteries behind Saturn's apparently elusive X-ray aurora.